Facile synthesis of zero valent iron and photocatalytic application for the degradation of dyes - Haq N Bhatti; Zunaira Iram; Munawar Iqbal; Jan Nisar; M I Khan (Materials Research Express, 2020)
In the present investigation, Zero valent iron (ZVI) was synthesized using ferrous sulfate and borohydrate in the presence of EDTA and characterized by x-ray Diffraction (XRD), Energy-dispersive x-ray (EDX) and Scanning electron microscope (SEM) techniques. The prepared ZVI catalytic activity was evaluated by degrading Acid Red 1 (AR1) and Acid Green 25 (AG25) dyes. The process variables such as pH, initial dye concentration, ZVI dose, contact time, hydrogen peroxide (H _2 O _2 ) and temperature were optimized for maximum dye degradation. AG25 removal was 98% at pH 4, ZVI dose 0.2 g l ^−1 , initial dye concentration 50 mg l ^−1 , 90 min reaction time and 8 mM H _2 O _2 concentration, whereas pH 2, ZVI dose 0.1 g l ^−1 , 50 mg l ^−1 initial dye concentration, 8 mM H _2 O _2 and 90 min were found to be optimum for AR1 maximum degradation of 91.60%. Behnajady–Modirshahla–Ghanbery kinetic model and thermodynamic study revealed the spontaneity and endothermic nature of the process. Results revealed that ZVI has potential to degrade the dyes and could possibly be used for the degradation of dyes in wastewater.